2012
DOI: 10.1038/ismej.2012.19
|View full text |Cite
|
Sign up to set email alerts
|

Changes in coral microbial communities in response to a natural pH gradient

Abstract: Surface seawater pH is currently 0.1 units lower than pre-industrial values and is projected to decrease by up to 0.4 units by the end of the century. This acidification has the potential to cause significant perturbations to the physiology of ocean organisms, particularly those such as corals that build their skeletons/shells from calcium carbonate. Reduced ocean pH could also have an impact on the coral microbial community, and thus may affect coral physiology and health. Most of the studies to date have exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 71 publications
6
77
0
1
Order By: Relevance
“…Cladocora caespitosa was also included in our study considering samples from the Western Mediterranean (Castellón and Tarragona, Balearic Sea); however, they harbor the Symbiodinium sp. "Temperate A" clade, which differs from that found by LaJeunesse et al (2012) and Meron et al (2012). This regional variation in Symbiodinium associations within the same host species has been previously reported in the Western Atlantic as well as the Indo-Pacific Oceans, suggesting that those changes might be dependent on regional environmental conditions (Rodriguez-Lanetty et al 2001;Savage et al 2002).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Cladocora caespitosa was also included in our study considering samples from the Western Mediterranean (Castellón and Tarragona, Balearic Sea); however, they harbor the Symbiodinium sp. "Temperate A" clade, which differs from that found by LaJeunesse et al (2012) and Meron et al (2012). This regional variation in Symbiodinium associations within the same host species has been previously reported in the Western Atlantic as well as the Indo-Pacific Oceans, suggesting that those changes might be dependent on regional environmental conditions (Rodriguez-Lanetty et al 2001;Savage et al 2002).…”
Section: Resultssupporting
confidence: 56%
“…Symbiodinium phylotype B has also been described by (2012) found phylotype B2 in three species of scleractinians from the coast of Israel in the Eastern Mediterranean Basin: Oculina patagonica, Cladocora caespitosa and Madracis pharensis. In addition, Meron et al (2012) found this same phylotype in Balanophyllia europaea and C. caespitosa in the Central Mediterranean (Iscchia Island, Southern Tyrrhenian Sea). However, these authors also found clade "Temperate A" in some individuals of B. europaea from the same locality.…”
Section: Resultsmentioning
confidence: 60%
“…For example, O. faveolata's microbiome did not significantly shift when the host bleached (Tracy et al, 2015). Furthermore, coralassociated microbial communities did not undergo major shifts when transplanted to a natural lower pH environment and did not harbor microbial pathogens (Meron et al, 2012). This study (Meron et al, 2012), suggests that for these two coral species (i.e., Balanophyllia europaea and Cladocora caespitosa), reduced pH does not pose a significant threat to coral health.…”
Section: Stressors Increase Opportunistic and Pathogenic Bacterial Tamentioning
confidence: 75%
“…Furthermore, coralassociated microbial communities did not undergo major shifts when transplanted to a natural lower pH environment and did not harbor microbial pathogens (Meron et al, 2012). This study (Meron et al, 2012), suggests that for these two coral species (i.e., Balanophyllia europaea and Cladocora caespitosa), reduced pH does not pose a significant threat to coral health. Importantly, environmental conditions can buffer these microbiome changes, specifically with high water flow buffering coral microbiome changes under high temperatures (Lee et al, 2017).…”
Section: Stressors Increase Opportunistic and Pathogenic Bacterial Tamentioning
confidence: 78%
See 1 more Smart Citation